Circulating α-Klotho Levels in Hemodialysis Patients and Their Relationship to Atherosclerosis - Ling Yu; Li Kang; Xiao-Zhuan Ren; Zong-Li Diao; Wen-Hu Liu (Karger Publishers, 2018)
Background/Aims: Serum soluble Klotho (sKlotho) plays a role in cardiovascular disease in some populations. However, information regarding the effect of serum sKlotho on atherosclerosis in patients on maintenance hemodialysis (MHD) is limited. Therefore, we tested the level of serum sKlotho in MHD patients to investigate atherosclerosis disease and determine the relationship between sKlotho and atherosclerosis. Methods: Using cross-sectional research, anthropometric and laboratory data were collected for 330 MHD patients. The levels of serum sKlotho before dialysis were tested by enzyme-linked immunosorbent assay. Carotid intima-middle thickness (cIMT) and the number of carotid artery atherosclerotic plaques were measured by color Doppler ultrasonography. The risk factors of atherosclerosis were explored by multivariate logistic regression analysis. Results: Among 330 MHD patients, the average serum sKlotho was (379.93±143.66) pg/ml. The level of serum sKlotho was positively related to hemoglobin (P< 0.05). It was negatively correlated with systolic pressure, pulse pressure, ultrafiltration volume, serum phosphorus, corrected serum calcium×phosphorus, high-sensitivity C-reactive protein (Hs-CRP), cIMT and carotid atherosclerotic plaque quantity and atherosclerosis (P< 0.05). Multivariate logistic regression analysis showed that age (OR = 1.108, 95% CI = 1.067 ∼ 1.151, P = 0.000), dry weight (OR = 1.050, 95% CI = 1.014 ∼ 1.088, P = 0.007), Hs-CRP (OR = 1.126, 95% CI = 1.005 ∼ 1.261, P = 0.041), and serum sKlotho (OR = 0.997, 95% CI = 0.995 ∼ 1.000, P = 0.032) were risk factors for atherosclerosis in MHD patients. Conclusion: Serum sKlotho was related to systolic pressure, pulse pressure, ultrafiltration volume, hemoglobin, serum phosphorus, corrected serum calcium×phosphorus, Hs-CRP, increased cIMT, carotid atherosclerotic plaque quantity and atherosclerosis. Age, dry weight, Hs-CRP, and serum sKlotho were risk factors for atherosclerosis in MHD patients. Serum sKlotho may be a novel risk factor for atherosclerosis in MHD patients.